Prediksi Klasifikasi Perawatan pada Dataset Kanker Payudara Coimbra Memakai Metode Naive Bayes - Ferawaty, Ferawaty; Chandra, Wenripin; Ivanka, Kelvin (UNIVERSITAS PELITA HARAPAN, 2020)
Breast cancer is a dreaded disease and a major cause of death. In this study, the NaÃ¯ve Bayes method is used to predict the category of breast cancer treatment for the Breast Cancer Coimbra Dataset. Test results involving nine variables in the dataset resulted in 44.8% of the